Global Properties of the Metabolic Map of Escherichia coli - Ouzounis, Christos A.; Karp, Peter D. (Genome Research, 2000)
The EcoCyc database characterizes the known network ofEscherichia coli small-molecule metabolism. Here we present a computational analysis of the global properties of that network, which consists of 744 reactions that are catalyzed by 607 enzymes. The reactions are organized into 131 pathways. Of the metabolic enzymes, 100 are multifunctional, and 68 of the reactions are catalyzed by >1 enzyme. The network contains 791 chemical substrates. Other properties considered by the analysis include the distribution of enzyme subunit organization, and the distribution of modulators of enzyme activity and of enzyme cofactors. The dimensions chosen for this analysis can be employed for comparative functional analysis of complete genomes.
10.1101/gr.10.4.568